Effect of germination on biochemical changes in high yielding barley (Hordium vulgare L.) varieties - Rahman, MM; Salam, SS Binte; Shahjadee, U Fatema; Rupa, A Zerin; Rahman, M Mashiar; Azad, A Kalam (Bangladesh Journal of Scientific and Industrial Research, 2018)
The effect of germination was evaluated on the nutritional properties and enzyme activities of three barley (Hordium vulgare L.) varieties namely BARI Barley-4, BARI Barley-5 and BARI Barley-7 produced by Bangladesh Agricultural Research Institute (BARI). The nutritional compositions and enzymatic activities (α-amylase and protease) in both raw and germinated seeds were changed gradually with germination period. Protein content of germinated seeds for BB-4, BB-5 and BB-7 was recorded as 13.65%, 14.34% and 13.95% respectively. Maximum increase of protein was 20.81% for BB-5 at 48 hours of germination. Gradual decrease was observed at 72 hours of germination and maximum decrease was 7.66% for BB-5 but protein content was higher than non germinated seeds. Enzyme activity of α-amylase and protease showed the results 2.20 U/g BB-5 and 1.16 U/g BB-4. Highest increase of α-amylase and protease activity were found 125.53% for BB-7 and 107.55% for BB-5 at 48 hours of germination. The highest amount of total and reducing sugar was 12.58% for BB-5 and 1.97% for BB-7 respectively at 72 hours of germination. The maximum increase of total sugar was 240.00% and in reducing sugar it was 79.09% for BB-5 and BB-7 respectively. Highest calcium, phosphorus and iron contents were 39.70 (mg/100g), 273.91 (mg/100g) and 8.37 (mg/100g) for BB-4 and BB-7 respectively. The maximum increases of calcium and iron contents were 33.26% and 85.58% for BB-4 and BB-7 respectively at 48 hours of germination. Germinated barley seeds contain more protein with other easily digestible biomolecule than non germinated seeds. Bangladesh J. Sci. Ind. Res.53(4), 311-318, 2018